Analysis of the Effect of Work Stress, Internal Conflict and Organizational Culture towards Employee Productivity in Budi Artha Cooperatives (KSU) Alor District - Hermayanti Hermayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Analysis of the Effect of Work Stress, Internal Conflict and Organizational Culture on Employee Productivity Budi Artha Alor Regency with tThe aim of the study was to determine the effect of work stress, internal conflict, and organizational culture onEmployee Productivity of Budi Artha, Alor Regency for the 2017-2021 Period.The sampling technique used is multiple linear regression analysis with the SPSS program, in this study using data collection techniques, namely by distributing statements to all employees in the Budi Artha multi-business cooperative (KSU). And the sampling technique used is a saturated sample because employees are used as samples and the data obtained         as many as 78 respondents. Based on the results of the analysis of multiple linear regression test data in this study, it is known that the significance value is 0.000. And the constant value is 0.936. ThereforeThe results of hypothesis testing are in accordance with the variables of work stress, internal conflict and organizational culture have an effect on the variable of employee productivity (Y). This is evidenced by statistical tests through the f test with a significance level of 5% which has a probability value of 0.000 <0.05, this means that work stress, internal conflict and organizational culture simultaneously affect employee productivity. Thus, accepting the Alternative Hypothesis (Ha) and rejecting the null hypothesis (H0)